EFFECT OF STRESS MANAGEMENT ON LEVEL OF DEPRESSION, ANXIETY AND STRESS IN CARDIOVASCULAR DISEASE PATIENTS - KHAN , MA; GUL , R; IRSHAD , E (Biological and Clinical Sciences Research Journal, 2024)
Cardiovascular disease (CVD) remains a leading cause of morbidity and mortality worldwide, making holistic health management essential for patients. Psychological well-being, particularly stress, depression, and anxiety management, is critical for effective CVD rehabilitation. Interventions focused on stress management hold promise for reducing these negative psychological impacts, thereby enhancing patient health and recovery. Objective: This study aimed to evaluate the effect of a structured stress management intervention on reducing stress, depression, and anxiety levels in patients with cardiovascular disease. Methods: A pretest-posttest design with a control group was employed to assess the impact of stress management on mental health outcomes in CVD patients. Sixty patients with CVD were recruited from a private and a government hospital in Rawalpindi, Pakistan, in 2023. Patients were randomly assigned to either a control group (n=30) or an intervention group (n=30). The intervention group participated in eight weekly 90-minute sessions focused on stress, thought-feeling connections, relaxation techniques, cognitive distortion detection, management of anxiety and depression, social relations enhancement, and effective coping strategies. Data were collected at baseline (pretest), 1.5 months, and 3 months post-intervention using validated scales to measure anxiety, stress, and depression levels. The control group received standard care without any psychological intervention. Statistical analysis was performed using SPSS version 25, and repeated measures ANOVA was applied to evaluate changes in stress, depression, and anxiety levels over time. Results: The results revealed a significant reduction in stress, depression, and anxiety levels in the intervention group compared to the control group (p<0.05). Participants who underwent the stress management intervention showed substantial improvement in psychological well-being at both the 1.5-month and 3-month follow-ups. Conclusion: The stress management intervention demonstrated a significant positive impact on reducing anxiety, stress, and depression in CVD patients. These findings highlight the value of incorporating structured psychological support as a part of comprehensive care for cardiovascular patients, providing essential guidance for healthcare practitioners to enhance patient outcomes through holistic care.